Dilution of botulinum toxin type A in local anesthetics: a therapeutic opportunity in migraine treatment - Nogueira, Eduardo de Almeida Guimarães; Piovesan, Elcio Juliato; Peres, Mario Fernando Prieto (Headache Medicine, 2024)
Botulinum Toxin (BoNT) type A, derived from Clostridium botulinum, is widely employed in neurology for its muscle-paralyzing effects. Concurrently, local anesthetics like lidocaine offer regional pain relief. Combining BoNT-A with local anesthetics could enhance therapeutic efficacy, particularly in headache disorders. We conducted a systematic review following PRISMA guidelines, searching various databases for relevant studies. Among the 1,623 articles initially identified, 13 met inclusion criteria. Notably, no trials specifically addressed BoNT-A dilution in local anesthetics for headaches. However, studies in other contexts revealed promising findings. For instance, blending BoNT-A with Lidocaine and epinephrine demonstrated superior pharmacological properties compared to saline reconstitution. Nonetheless, caution is warranted, as fatal outcomes have been reported with BoNT-A and lidocaine administration. While the literature on BoNT-A diluted in local anesthetics for migraines is scarce, existing evidence suggests potential benefits akin to other disorders. Reconstituting BoNT-A in lidocaine offers a promising avenue for optimizing headache treatment, warranting further investigation in future research endeavors.